Dampak Pariwisata terhadap Pertanian di NTT: Perspektif Analisis Input-Output - Diah Mekita Sari; Dwi Rizky Syaifullah (Jurnal Statistika Terapan (ISSN 2807-6214), 2024)
The agriculture sector has been the largest contributor to Gross Regional Domestic Product (GRDP) in the Province of Nusa Tenggara Timur (NTT) for over a decade. Additionally, the agriculture sector absorbs the highest number of labor and serves as the primary livelihood for the impoverished population in NTT. Alongside its focus on agriculture, the NTT provincial government is also prioritizing tourism development as a new economic driver. This is due to the challenges faced by the agriculture sector, which remains the primary pillar of the economy in NTT, including land conversion, climate change, limited infrastructure, and low productivity. Research on the impact of tourism on the agriculture sector in Indonesia, particularly in NTT, remains limited. Therefore, this study aims to analyze the impact of tourist expenditure on the agriculture sector in the Province of NTT using an Input-Output (I-O) table approach. The study employed descriptive analysis through graphs derived from output multiplier analysis, value-added (Nilai Tambah Bruto, NTB), income/wages, and labor absorption related to tourist expenditure. The findings indicated that tourist expenditure did not have a direct impact on the agriculture sector in NTT. The agriculture sector experienced indirect impacts in terms of output, NTB, wages, and labor absorption resulting from tourism activities. The impact of tourism expenditure on agricultural output was relatively small, given that agriculture is a primary sector providing raw materials to sectors related to tourist needs. The impact of tourism expenditure on NTB in the agriculture sector was relatively high. However, the impact of tourism expenditure on wages in the agriculture sector was relatively low. Conversely, the impact of tourism expenditure on labor absorption was relatively high.